Fundamentals, progress and perspectives on high-frequency phononic crystals. (28th January 2022) - Cang, Yu; Jin, Yabin; Djafari-Rouhani, Bahram; Fytas, George
Abstract: Phononic crystals (PnCs) are capable of manipulating the flow of elastic energy through their periodic structures and have emerged as a promising field in the last two decades. Thanks to the advances in microfabrication technologies and developments of multifunctional materials, the engineering of periodic structures moves forward to the nanometer scale. Hence, the relevant frequencies of elastic waves are pushed toward the gigahertz regime where strong photon-phonon interactions trigger the applications of PnCs towards information and communication technologies. In this review, we present the experimental achievements on hypersonic PnCs involving microfabrication technologies to realize the desired structures and characterization of their band structures for unraveling phonon propagation modulation. Some application-oriented research directions are proposed in terms of advances in fabrication and characterization technologies and the development of electro-optomechanical systems.